The Development of Creambath Preparation with Combination of Garlic Extract (Allium sativum L.) and Custard Apple Seeds Extract (Annona squamosa L.) as Anti-Dandruff and Anti Head Lice (Pediculus humanus capitis) - Mudita Mudita; Swasono R Tamat; Agung Eru Wibowo (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Allicin and ajoene are active compounds in garlic which have proven to be of benefit as antifungal. Meanwhile, the content of oleic acid and triglycerides from the custard apple seeds extract showed anti-fungal activity in vitro. This study aimed to obtain a preparation of creambath combination of garlic extract and custard apple seeds extract which have anti-dandruff and anti head lice activity. Garlic extract was obtained by adding phosphate buffer with freeze-dry method, while custard apple seeds extract was obtained from maceration using petroleum ether. Garlic extract provides an anti-dandruff effect with a minimum inhibitory concentration (MIC) of 6.25 mg/mL and the smallest custard apple seeds extract (LD 100%, 3 hours) which is 3.13 mg/mL can provide anti head lice effect. Variations in the concentration of the combination of garlic extract and custard apple seeds extract used in creambath preparations were (6.25 mg/mL and 3.13 mg/mL), (12.5 mg/mL and 6.25 mg/mL) and (25 mg/mL and 12.5 mg/mL). The resulting creambath preparations have characteristics that are light green, green tea flavored, homogeneous, semisolid form, o/w cream type, pH 5.85-6.25, viscosity 34,000-72,000 cps with thixotropic pseudoplastic flow properties, average size particle 34.31-57.66 μm, anti-dandruff activity with diameters of inhibitory 9, 12, and 16 mm in 72 hours incubation time and LD 100% hair lice activity in 157, 133 and 105 minutes.